Pneumonias - Coelho, Liana Sousa [UNESP]; Tanni, Suzana Erico; Godoy, Irma de [UNESP] (My University, 2009)
Pneumonia is an infectious disease with great morbidity and mortality worldwide. According to the current guidelines recommendations the authors reviewed the treatment of community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP). In this paper will be presented data about etiology, clinics and diagnostic tools. © Copyright Moreira Jr. Editora.
Pneumonia
Keywords: Community acquired pneumonia; Hospital acquired pneumonia; Pneumonia; amoxicillin; amoxicillin plus clavulanic acid; amoxicillin plus sulbactam; antibiotic agent; astro; azi; azithromycin; cefepime; ceftazidime; ceftriaxone; cefuroxime axetil; chlorhexidine; cilastatin plus imipenem; ciprofloxacin; clarithromycin; clindal; clindamycin; imipenem; influenza vaccine; kefadim; levofloxacin; linezolid; maxcef; meropenem; moxifloxacin; novamox; penicillin G; piperacillin plus tazobactam; Pneumococcus vaccine; procaine penicillin; procin; qionoflox; sigma clav; sulbacter; sulbamox; sultamicillin; tamiram; tazidem; teicoplanin; triaxin; trifamox; unclassified drug; vancomicina; vancomycin; zinacel; alcoholism; antibiotic resistance; antibiotic therapy; bacterium culture; blood culture; bronchiectasis; bronchus obstruction; clinical feature; community acquired pneumonia; diagnostic test; dyspnea; Escherichia coli; fever; Haemophilus influenzae; hospital infection; hospitalization; human; influenza; Klebsiella pneumoniae; lung abscess; lung lavage; minimum inhibitory concentration; myalgia; Mycoplasma pneumoniae; pneumococcal infection; pneumonia; polymerase chain reaction; Proteus; pulse oximetry; risk factor; Serratia marcescens; Streptococcus pneumoniae; thorax radiography